Assessment of drought and soil moisture relationship: a case study in Cyprus using geospatial data - Neofytou, Eleni; Eliades, Marinos; Neophytides, Stelios P.; Papoutsa, Christiana; Kontoes, Charalampos; Hadjimitsis, Diofantos G. (My University, 2025)
Limited precipitation events may result in soil moisture depletion and to an overall water scarcity over a catchment areas. Forest productivity and functioning are severely influenced by drought conditions, which in some cases can even result in tree mortality. Thus, monitoring drought conditions in forested areas is essential given their critical environmental importance. The aim of this research is to identify drought events occurred in forested areas in the semi-arid island of Cyprus and its relationship with soil moisture at different depths using geospatial data. The current study used the 3-month period Standardized Precipitation Evapotranspiration index (SPEI) data for drought monitoring and GLDAS datasets, for soil moisture depths of 0-10cm, 10-40cm, 40-100cm and 100-200cm. A correlation analysis was performed to observe the relationship of SPEI with the different soil moisture depths. Pearson correlation analysis showed moderate to strong positive (0.325-0.549) linear relationship between SPEI and soil moisture at different depths with the correlation becoming stronger at deeper soil profiles. Spearman correlation analysis showed a weak to moderate positive monotonic relationship (0.294-0.439) with the correlation becoming stronger at deeper soil profiles.